Crossectomy and Foam Sclerotherapy of the Great Saphenous Vein versus Stripping of Great Saphenous Vein and Varicectomy in the Treatment of the Legs Ulcers. (16th December 2013) - Delgado-Beltran, Alvaro
Abstract : Objective . To show our results in the surgical treatment of legs varicose ulcers, with crossectomy and foam sclerotherapy (CAFE) of the great saphenous vein (GSV) in group I and stripping of GSV and varicectomy in group II. Methods . 35 patients with active venous leg ulcers were recruited and treated. They were collected in two groups. Group I were treated by crossectomy and foam sclerotherapy of the GSV and group II were treated by stripping of GSV and varicectomy. The healing time of the ulcer and the complications were recorded after the procedure in the follow-up visits. Results . 29 out of the 35 patients completed the follow-up. There were eight cases of incomplete healing of the leg ulcer, 4 in group I (19.04%) and 4 in group II (40%), P < 0.05 . The average rate of healing in group I was 0.38 cm/day and 0.13 in group II, P < 0.05 . Conclusion . CAFE technique of the great saphenous vein in the treatment of 6 CEAP patients is a procedure that improves the rate of ulcer healing as compared to these two groups. It is a safe and reliable minimally invasive method, with less morbidity.